Investment policy trends - Shevtsova A. V., Vasileva D. A. (Scientific research and developments of students, 2018)
the article points out that investment policy becomes more complex, heterogeneous and uncertain. The imperatives of sustainable development pose new challenges to investment policies and make them more multifaceted, and their approaches become more diversified. The authors say that this makes investment policy less predictable in the eyes of investors.
Keywords: инвестиционная политика; investment policy; ограничения или нормы регулирования в инвестиционной сфере; руководящие принципы глобальной инвестиционной политики; модернизация существующих контрактов старых поколений; restrictions or norms of regulation in the investment sphere; guiding principles of the Global Investment policy; modernization of existing contracts of old generations